Non-Nutritive Polyol Sweeteners Differ in Insecticidal Activity When Ingested by Adult Drosophila melanogaster (Diptera: Drosophilidae). Issue 1 (7th June 2016) - O'Donnell, Sean; Baudier, Kaitlin; Marenda, Daniel R.
Abstract: Previous work showed the non-nutritive polyol sweetener Erythritol was toxic when ingested by Drosophila melanogaster (Meigen, 1930). This study assessed whether insect toxicity is a general property of polyols. Among tested compounds, toxicity was highest for erythritol. Adult fruit flies ( D. melanogaster ) fed erythritol had reduced longevity relative to controls. Other polyols did not reduce longevity; the only exception was a weaker but significant reduction of female (but not male) longevity when flies were fed D-mannitol. We conclude at least some non-nutritive polyols are not toxic to adult D. melanogaster when ingested for 17 days. The longer time course (relative to erythritol) and female specificity of D-mannitol mortality suggests different mechanisms for D-mannitol and erythritol toxicity to D. melanogaster .